Behavioural repeatability in Sardinian warblers (Sylvia melanocephala): larger individuals are more aggressive - Beltrão, Patrícia (2021)
Birds can behave aggressively towards conspecifics to defend a territory and to compete for access to food and mates. The effects of phenotypes, such as sex and age, in aggressive behaviour have not yet been fully understood. Moreover, differences in aggression levels can reflect alternative behavioural strategies (i.e. proactive–reactive axis). We aimed to understand the relation between aggressive behaviour and different phenotypes (i.e. age, sex, body size) and between behaviours present in the proactive–reactive axis (i.e. aggression, exploration and fear). We studied the behaviour of a highly territorial species that shows sexual dimorphism, the Sardinian warbler (Sylvia melanocephala), using four behavioural tests: mirror, exploration, predation and tonic immobility. The tests measured respectively aggression, exploration and fear (the last two). Our results showed that the studied behaviours were not related to each other, suggesting an absence of the proactive–reactive axis. Only body size was found to predict aggressive behaviour, which might signal fighting ability in this species. Males and females did not differ in their aggression levels, suggesting that both sexes might play a role in territory defence. These results may reflect the importance of territorial defence in both sexes for species evolution.